Association Between Mesiodistal Tooth Width and Soft Tissue Facial Profile Convexity among Chinese Adolescents in Jember, Indonesia - Taqwim, Ali; Rohmah, Fatihatur; Netiani, Ernita; Utami, Mellyna Trismi (Journal of Dental and Biosciences, 2026)
B Background: Tooth size and soft tissue facial profile are influenced by genetic, sexual, and ethnic factors. Understanding their relationship is important for orthodontic diagnosis, particularly in specific ethnic populations. Methods: A cross-sectional study was conducted on 50 Chinese adolescents (25 males, 25 females) aged 17-18 years. Mesiodistal tooth width from maxillary and mandibular central incisors to first molars was measured on dental casts. Soft tissue facial profile convexity was assessed using standardized lateral facial photographs. Sex differences were analyzed using independent t-tests, while associations were evaluated using Pearson correlation and linear regression (α = 0.05). Results: Males exhibited significantly larger mesiodistal tooth widths than females in both arches (p < 0.05). No significant sex differences were observed in facial profile convexity (p > 0.05). A weak but statistically significant negative correlation was found between mesiodistal tooth width and facial profile convexity (r = −0.35 maxilla; −0.34 mandible), accounting for 12.2% of the variance. Conclusion: Mesiodistal tooth width demonstrated a weak association with soft tissue facial profile convexity among Chinese adolescents in Indonesia, indicating that mesiodistal tooth width alone has limited predictive value for facial profile morphology and supporting the multifactorial basis of facial esthetics. Key words: Mesiodistal tooth width; soft tissue facial profile; facial convexity; Chinese ethnicity